Contributing factors to white collar crime based on managerial perspective / Asmawati Idris and Rozainah Hamiddon - Idris, Asmawati; Hamiddon, Rozainah (2013)
This paper presents finding of a study that was carried out in September 2012 at Kota Kinabalu to study on the contributing factors committing to white collar crime based on managerial perspective. 150 employers supposed to be surveyed, however only 125 employers had answering our questionnaires, which 52 were males and 73 were females. The population of employees at public and private sector in Kota Kinabalu and strata sampling been used to select respondent from managerial level. A survey questionnaire was administered to them and collected on its completion. Frequencies and nonparametric spearman's correlation were used in analysis the data.